Master Robotic Net - Vladimir Lipunov; Victor Kornilov; Evgeny Gorbovskoy; Nikolaj Shatskij; Dmitry Kuvshinov; Nataly Tyurina; Alexander Belinski; Alexander Krylov; Pavel Balanutsa; Vadim Chazov; Artem Kuznetsov; Petr Kortunov; et al. (Advances in Astronomy)
The main goal of the MASTER-Net project is to produce a unique fast sky survey with all sky observed over a single night down to a limiting magnitude of 19-20. Such a survey will make it possible to address a number of fundamental problems: search for dark energy via the discovery and photometry of supernovae (including SNIa), search for exoplanets, microlensing effects, discovery of minor bodies in the Solar System, and space-junk monitoring. All MASTER telescopes can be guided by alerts, and we plan to observe prompt optical emission from gamma-ray bursts synchronously in several filters and in several polarization planes.